2012
DOI: 10.1172/jci63060
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted cortical function underlies behavior dysfunction due to social isolation

Abstract: Stressful events during early childhood can have a profound lifelong influence on emotional and cognitive behaviors. However, the mechanisms by which stress affects neonatal brain circuit formation are poorly understood. Here, we show that neonatal social isolation disrupts molecular, cellular, and circuit developmental processes, leading to behavioral dysfunction. Neonatal isolation prevented long-term potentiation and experience-dependent synaptic trafficking of α-amino-3-hydroxy-5-methylisoxazole-4-propioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
60
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 65 publications
3
60
0
Order By: Relevance
“…2B). This result is consistent with other studies demonstrating the glucocorticoid signaling dependence of stress-induced alterations in glutamate transmission (9,28).…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…2B). This result is consistent with other studies demonstrating the glucocorticoid signaling dependence of stress-induced alterations in glutamate transmission (9,28).…”
Section: Resultssupporting
confidence: 93%
“…We found that the mEPSCs of socially isolated animals exhibited reduced amplitudes compared with those of nonisolated control rats ( Fig. 2A), similar to the previous finding in the developing barrel cortex (9). Consistent with these electrophysiological results, we detected reduced levels of GluA1 in the postsynaptic density (PSD) fraction of the mPFC from isolated animals compared with nonisolated animals (Fig.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations